2013
DOI: 10.1111/jonm.12044
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of job satisfaction on turnover intention for long-term care nurses in Taiwan

Abstract: This study provides nursing administrators with a resource to build a supportive environment to increase nurses' job satisfaction and to decrease their stress and turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
113
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 39 publications
14
113
0
9
Order By: Relevance
“…), and obtaining and maintaining these resources is related to lower levels of burnout. Prior research (Leka & Jain, 2010; Moura et al, 2014; Scanlan & Still, 2013) has reported that the reduction of burnout syndrome leads to greater job satisfaction, a variable that is recognized not only for its mediating role between work stress factors and TI (Ferreira et al, 2017; Kuo et al, 2014), but also for its potential to decrease withdrawal cognitions in different occupational groups (Allisey et al, 2014). On the contrary, the results suggest that low justice perceptions produce a feeling of lack of control over work conditions and outcomes, thus generating an increase in burnout and a decrease in job satisfaction, which in turn fuels TI among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), and obtaining and maintaining these resources is related to lower levels of burnout. Prior research (Leka & Jain, 2010; Moura et al, 2014; Scanlan & Still, 2013) has reported that the reduction of burnout syndrome leads to greater job satisfaction, a variable that is recognized not only for its mediating role between work stress factors and TI (Ferreira et al, 2017; Kuo et al, 2014), but also for its potential to decrease withdrawal cognitions in different occupational groups (Allisey et al, 2014). On the contrary, the results suggest that low justice perceptions produce a feeling of lack of control over work conditions and outcomes, thus generating an increase in burnout and a decrease in job satisfaction, which in turn fuels TI among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Also, based on a sample of Pakistani engineers and supervisors, Shaukat, Yousaf, and Sanders (2017) used structural equation modeling to prove that burnout mediated the association between relationship conflict and different outcome variables, including TI. Regarding job satisfaction as a mediator variable, Kuo et al (2014) showed that it significantly mediated the relationship between work stress and TI among long-term care nurses in Taiwan. Also, drawing on data from a sample of Chinese nurses, Feng, Su, Yang, Xia, and Su (2017) observed that social status exerted significant indirect effects on TI through job satisfaction.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have also analyzed the mediating role of job satisfaction (i.e. Yousef, 2002;Wouter, 2009;Kuo, Lin, & Li, 2013). Hence, we can assume that job satisfaction will mediate the relationship between coworker support for training and turnover intentions.…”
Section: Job Satisfaction As a Mediating Variablementioning
confidence: 99%